1982
DOI: 10.1115/1.3162675
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Brittle Fracture

Abstract: Development of steeply dipping coal seam deposits of the Prokop'ev-Kiselov coal-bearing region of the Kuznets Basin introduces an important problem, i.e., calculation of the stressstrain state of a sloping-bedded rock mass. As has been demonstrated in a number of works, e.g., in [I], in many mechanics problems the rock mass may be modeled by an elastic uniform and isotropic material.The authors in [2] use these assumptions in order to analyze the stability horizontal workings in a slopping-bedded rock mass.In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
374
0
8

Year Published

1996
1996
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 606 publications
(398 citation statements)
references
References 0 publications
10
374
0
8
Order By: Relevance
“…where, C 44 , C 55 are the elastic constants, ρ is the mass density and W is the displacement component along Z (Cherepanov, 1979;Sih, 1968;Sih and MacDonald, 1964;Freund, 1998;Nian-Chun et al, 2004;2005;2006;Atkinson, 1975;1965). Using Atkinson transform (Nian-Chun et al, 2004;2005;2006;Atkinson, 1975;1965), it is found that Equation 2:…”
Section: Correlative Equations Of the Anti-plane Problem Concerning Ementioning
confidence: 99%
See 4 more Smart Citations
“…where, C 44 , C 55 are the elastic constants, ρ is the mass density and W is the displacement component along Z (Cherepanov, 1979;Sih, 1968;Sih and MacDonald, 1964;Freund, 1998;Nian-Chun et al, 2004;2005;2006;Atkinson, 1975;1965). Using Atkinson transform (Nian-Chun et al, 2004;2005;2006;Atkinson, 1975;1965), it is found that Equation 2:…”
Section: Correlative Equations Of the Anti-plane Problem Concerning Ementioning
confidence: 99%
“…When T(η) = i (C -ρη ) C , in order to represent expediently, therefore the positive root is taken. Here exists (Cherepanov, 1979;Nian-Chun et al, 2004;2005;2006;Atkinson, 1975):…”
Section: Correlative Equations Of the Anti-plane Problem Concerning Ementioning
confidence: 99%
See 3 more Smart Citations